Surgically-managed supraventricular tachycardia in a division II men`s basketball player - Holzberger, K. L.; Keeley, K.; Donahue, M. (International Journal of Athletic Therapy & Training, 2018)
During practice, a 25-year-old Division II men`s basketball player reported lightheadedness, blurry vision, and that his heart was "racing". After his heart rate was recorded above 240 bpm on two occasions, the athlete was referred for further evaluation. An electrophysiologist diagnosed the patient with supraventricular tachycardia (SVT). The condition was corrected using a catheter radiofrequency ablation and the athlete returned to play 5 weeks after his first presentation of signs and symptoms. The referral, diagnostic, treatment, and return-to-play processes demonstrated in this case represent the successful use of interprofessional practice to manage an athlete with SVT.